2018
DOI: 10.1155/2018/7530602
|View full text |Cite
|
Sign up to set email alerts
|

Telemedical Coaching Improves Long-Term Weight Loss in Overweight Persons: A Randomized Controlled Trial

Abstract: Background Lifestyle interventions have shown to be effective when continuous personal support was provided. However, there is lack of knowledge whether a telemedical-approach with personal coaching contributes to long-term weight losses in overweight employees. We, therefore, tested the hypothesis that telemedical-based lifestyle interventions accompanied with telemedical coaching lead to larger weight losses in overweight persons in an occupational health care setting. Methods Overweight employees (n=180) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Telemedical coaching . The education program was continuously supported by telemedically supported coaching [ 25 ]. Coaching sessions included information about coping strategies for lifestyle changes, healthy diet for maintaining insulin levels low, physical activity, motivation and overweight or obesity-related diseases like type 2 diabetes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Telemedical coaching . The education program was continuously supported by telemedically supported coaching [ 25 ]. Coaching sessions included information about coping strategies for lifestyle changes, healthy diet for maintaining insulin levels low, physical activity, motivation and overweight or obesity-related diseases like type 2 diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…Data, which had been acquired from the telemetric devices (which could be monitored by coaches and participants during the whole study), were discussed within the coaching sessions (i.e., steps, weight). Furthermore, participants were motivated to achieve their individually determined goals (i.e., weight goals, step counts) using the medical mental motivation program [ 25 , 27 ], and negative developments regarding recorded data were evaluated and discussed with the participants. Therefore, coaching sessions were also used to increase the study compliance and adherence of probands by coaches.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin in overweight patients does not only suppress lipolysis but also slows down fat absorbtion. Unfortunately, insulin makes it more effectively when the body weight is higher, which was reported by a research team from Basel University Clinic (156,159). It was shown that glucose load in patients with body mass index ≥ 30 kg/m 2 increases the level of insulin more than when BMI ≤ 25 kg/m 2 .…”
Section: K E T O G E N I C D I E T F O R R E D U C T I O N O F W E I mentioning
confidence: 98%
“…The target can be achieved not only in T2D patients, but also in people, only susceptible to overweight. According to a recently published research in Dusseldorf (156), where the use of an intervention program aimed at changing the way of life under supervision of a medical team led to a significant loss of weight and improved metabolic control in overweight patients at risk for diabetes.…”
Section: K E T O G E N I C D I E T F O R R E D U C T I O N O F W E I mentioning
confidence: 99%